Steps To Grow Your Wealth Steadily By Investing In Monthly Income Plan Of Mutual Funds - Pushpa Raj K, Dr. B. Shyamala Devi (International Journal of Advanced Science and Technology, 2020)
The Primary Objective Of This Study Is To Identify The Top Performing Monthly Income Plan Among The Selected List Of Mip Mutual Funds Available In India. In Mutual Funds, Mips Are One Such Category Which Invests Majorly In Debt Oriented Funds And Very Less Or Little Exposure Towards Equity Funds. Making Investment Under Mips Is Considered As Lessrisky With Higher Potential Returns.Monthly Income Plans Are Launched With The Intent Of Providing Monthly Income To Its Investors On Regular Basis. The Investors Choose The Periodicity Of The Payments - Generally Like Monthly, Quarterly, Half Yearly And Annually.A Growth Option Is Also Available For The Investors. In Growth Option, The Investors Will Not Be Receiving The Dividends In Monthly Income But For The Purpose Of Increasing Their Gains In The Form Of Capital Appreciation. In This Study, We Are Going To Evaluate The Performance Of The Selected Mips Under Hybrid Mutual Funds Category. The Risk Ratios Of These Funds Like Sharpe Ratio, Beta And Standard Deviations Have Also Been Analyzed. This Study Concludes With The Identification Of Top Performing Mip Under Hybrid Mutual Funds Including Their Volatility And Returns Yielded Per Each Unit Of Risk.